Clinical review of humic acid as an antiviral: Leadup to translational applications in clinical humeomics - Socol, David C. (Frontiers in Pharmacology, 2023)
This clinical review presents what is known about the antiviral features of humic substances (HS) to the benefit of the clinical healthcare provider using available data in humeomics, the study of the soil humeome. It provides the reader with a working framework of historical studies and includes clinically relevant data with the goal of providing a broad appreciation of the antiviral potential of humic substances while also preparing for a translational leap into the clinical application of humic acid.